Investment opportunity set, dividend policy, company’s performance, and firm’s value: Some Indonesian firms evidence - Anggi Angga Resti; Budi Purwanto; Wita Juwita Ermawati (Jurnal Keuangan dan Perbankan, 2019)
The availability of investment opportunity set at state-owned companies and the dividend policy taken by state-owned company management should be signals in the company's efforts to improve performance.  Therefore, both the Investment Opportunity Set (IOS) and dividend policy can be factors driving corporate performance. Thus, state owned-companies can further enhance firm value. We examined the effect of the IOS and dividend policy on company performance and firm value. The sample used in this study was the state-owned company listed at the Indonesia Stock Exchange and observed for 5 years, from 2013 to 2017. Data were collected using a purposive sampling method. This study had 13 sample companies that were processed using the panel data regression method. We found the first result revealed that dividend policy had a positive effect on company performance, which had a positive effect on firm value. Besides, the IOS was observed to have a positive impact on firm value. The second result showed that the IOS did not affect the company's performance, and dividend policy did not influence the firm's value. Thus, those results proved that the company's performance could provide a signal to the firm's value.JEL Classification: G31, G32DOI: https://doi.org/10.26905/jkdp.v23i4.2753